ANALYSIS OF THE MARKET STRUCTURE OF HOSPITAL INDUSTRY IN INDONESIA - Rachmawati, Emma; Umniyatun, Yuyun; Kurniawan, Deni Wahyudi; Nurmansyah, Mochamad Iqbal; Pakkanna, Mukhaer; Nurjuman, Husnan; Budiarto, Slamet; Gohardi, Virgo Sulianto (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2024)
Background: Over the past decade, private investments in health care including hospital have grown significantly, more than doubling. As the number of hospitals in Indonesia increases, a competitive business environment develops. Identifying hospital market structure can help various stakeholders to optimize the hospital's performance. Aims: This study analyzed the market structure and concentration of the hospital industry in Indonesia. Methods: This study used hospital characteristics data from Ministry of Health of Indonesia that retrieved in October 2020. Market concentration is determined by the number of industry players operating in a market, the distribution of services, and the types of services offered. The hospital market concentration was identified by measuring the Concentration Ratio (CR) and the Herfindahl–Hirschman index (HHI). Results: The results showed that the market share of hospitals in Indonesia was still dominated by government hospitals, which represent 51.4% of the market share. The concentration ratio of four companies (CR4) remains <40, indicating that competition remains relatively open among private hospitals at the national level. Conclusion: Several cities have established hospital markets that are characterized by robust competition, whereas in other cities, the hospital industry remains oligopolistic or monopolistic. It is important to note, however, that this does not imply that the market structure is ineffective on account of competition; rather, it is the result of a scarcity of hospitals in a number of Indonesian cities. Keywords: Concentration ratio, Economic competition, Herfindahl–Hirschman Index, Hospital market